One-Dimensional Scanning of Electronic Wavefunction in Carbon Nanotubes by Molecular Encapsulation - Ye, Gui; Li, Jun; Deng, Ming-sen; Jiang, Jun (Chinese journal of chemical physics, 2015)
On the basis of first-principles calculations, we have designed a novel type of molecular systems in which a single-walled carbon nanotube (SWNT) is encapsulated by acyclic CB[n]-type molecular container. The electronic structures and coherent electron transportation properties of the molecules were simulated at the density functional theory level. Due to the weak interactions between the inner SWNT and outer molecular container, the acyclic part can slide along the nanotube direction, which in turn effectively changes the electron tunneling ability through the SWNT. The dependences of tunneling conductance on the position of the acyclic container attached to the SWNT were examined, which reflect clearly a Bloch form distribution of molecular wavefunction along the nanotube direction. We thus proposes a convenient way to scan the one-dimensional electron wavefunction in carbon nanotubes.